2023
DOI: 10.1021/acschemneuro.2c00487
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Structural and Binding Properties on Aβ Mature Fibrils Due to Histidine Protonation Behaviors

Abstract: Histidine tautomeric behaviors have been considered origin factors for controlling the structure and aggregation properties of misfolding peptides. Except for tautomeric behaviors, histidine protonation behaviors definitely have the same capacities due to the net charge changes and the various N/N–H orientations on imidazole rings. However, such phenomena are still unknown. In the current study, Aβ mature fibrils substituted with various protonation states were performed by molecular dynamics simulations to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…These findings indicate that the various histidine states have an impact on structural characteristics and aggregation. Our analysis of the Δ G 2 binding model confirmed that chains 1 and 6 barely interact, consistent with previous studies , that emphasize the crucial role of the main chain and adjacent chains in maintaining fibril stability.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings indicate that the various histidine states have an impact on structural characteristics and aggregation. Our analysis of the Δ G 2 binding model confirmed that chains 1 and 6 barely interact, consistent with previous studies , that emphasize the crucial role of the main chain and adjacent chains in maintaining fibril stability.…”
Section: Resultssupporting
confidence: 91%
“…59 Previous studies have also demonstrated that, in the substitution of middle chain of mature fibril, the H6 and H13 isomeric states directly influence the N-terminal H-bonding interaction networks, which in turn affect the interaction patterns between the various β-strands and the stability of the fibril. 56,60 However, the effect of histidine tautomerization behaviors on the edge chain of Aβ mature fibrils is not yet fully understood, although it has the potential to influence structural stability and aggregation characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histidine tautomeric behaviors involve isomerization between N‐ϵ (HIE, ϵ) and N‐δ (HID, δ), while protonation behaviors include both N‐ϵ (HIE, ϵ) and N‐δ (HID, δ) in a protonation state (denoted as (p) state) (Figure 1b). In an ideal vacuum, the ϵ/δ ratio is 1:0.16 [34,35] . However, histidine behaviors are highly susceptible to external factors, such as the pH environment, side chain interactions, and N/N−H atom orientation in the imidazole ring, which can result in significant fluctuations and diverse structural and aggregation features in realistic scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…38,39,[51][52][53][54][55][56] Histidine behavior in illnesses with misfolded proteins has been a significant problem in numerous research studies. [57][58][59][60] Owing to net charge shifts and varying N/N-H position on imidazole rings, histidine behaviors (containing tautomeric behaviors and protonation behaviors) are hypothesized to be a root cause of protein folding and/or misfolding 57,[60][61][62][63][64] (Scheme 1). In the imidazole ring, there are two intrinsically changeable isomeric forms (N-e (HIE, e) and N-d (HID, d) states) and a protonated form (both e and d states, described as p state) that play an active role in Ab misfolding.…”
Section: Introductionmentioning
confidence: 99%